2010
DOI: 10.1007/s00044-010-9465-4
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, and anticonvulsant activity of novel quinazolinone analogues

Abstract: A number of 2-substituted and 2,3-disubstituted quinazolinone analogues have been synthesized. Their structures have been elucidated on the basis of elemental analyses and spectroscopic studies (IR, 1 H NMR, and MS). An evaluation of the anticonvulsant activity of the prepared compounds has indicated that some of them exhibit moderate to significant activity, compared to diazepam and phenobarbital standards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Quinazolin‐4(3 H )‐ones (aka 4‐oxoquinazolines) are a structural sub‐category that have interesting properties such as antitumor ( e. g ., quinazolinone 1 ), anticonvulsant, and antitubercular behavior . In particular, 2‐cyanoquinazolin‐4(3 H )‐ones are useful synthetic scaffolds for the preparation of derivatives with anti‐inflammatory activity, antitumor derivatives of the natural product Luotonin A, and NMDA receptor antagonists .…”
Section: Introductionmentioning
confidence: 99%
“…Quinazolin‐4(3 H )‐ones (aka 4‐oxoquinazolines) are a structural sub‐category that have interesting properties such as antitumor ( e. g ., quinazolinone 1 ), anticonvulsant, and antitubercular behavior . In particular, 2‐cyanoquinazolin‐4(3 H )‐ones are useful synthetic scaffolds for the preparation of derivatives with anti‐inflammatory activity, antitumor derivatives of the natural product Luotonin A, and NMDA receptor antagonists .…”
Section: Introductionmentioning
confidence: 99%
“…We have reported that S ‐glycosylated hydantoin derivatives showed potent activity against the herpes simplex virus , the human immunodeficiency virus , and the leukemia subpanel . In continuation of our work on the synthesis of novel nucleosides as potential antiviral and antitumor agents and keeping in mind the biological significance of 2‐thioxoquinazolin‐4‐ones , we hereby report the synthesis and spectroscopy of a new series of S ‐alkylated and S ‐glycosylated 3‐substituted 2‐thioxo‐2,3‐dihydro‐1 H ‐benzo[ g ]quinazolin‐4‐one bases (Schemes and ). This is the first time to prepare S ‐glycosides of 3‐substituted 2‐thioxo‐2,3‐dihydro‐1 H ‐benzo[ g ]quinazolin‐4‐ones via new synthetic strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Quinazoline is one of the most frequently encountered heterocycles in medicinal chemistry. Quinazoline derivatives have shown significant biological activities such as analgesic , anti‐inflammatory , antifungal , antibacterial , anticancer , antitumor , anti‐HIV , antituberculosis , and anticonvulsant activities. Non‐proteinogenic amino acids are a major component in a number of drugs including β‐lactam antibiotics, glutamate antagonists, and antiviral drugs .…”
Section: Introductionmentioning
confidence: 99%